Motywy nadawania imion zwierzętom domowym w świetle Autobiografii na czterech łapach 1 Doroty Sumińskiej - Duszyk, Kinga (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2013)
Zoonymy is a relatively new branch of onomastics that deals with animal names. It is increasingly popular among scholars given the growing importance of pets in human life. No longer seen predominantly as a source of food, animals are now more than ever people’s best friends. It is reflected in the names that animal owners give their pets, which, in turn, are investigated by linguists. The article presents tendencies in the modern animal naming based on Autobiografia na czterech łapach [Autobiography on All Fours] by Dorota Sumińska.